Thermal and electrical performance of a hybrid design of a solar-thermoelectric system. (1st February 2017) - Ong, K.S.; Naghavi, M.S.; Lim, Christopher
Highlights: Hybrid solar-thermoelectric system studied under outdoor conditions. Electrical output voltage and hot water temperatures peaked around 15.30. Total electrical efficiency was very low, about 0.16% at around 15.30 h. Abstract: An evacuated tube heat pipe solar collector was fitted with four thermoelectric modules and four water cooling jackets on the condenser side to produce electricity and hot water simultaneously. Each cooling jacket had six mini water-flow channels inside it. Solar heat was absorbed and collected by the evaporator section. Experiments were conducted under outdoor environment with various water coolant flow rates. Once-through coolant water flow was adopted as a first step. Further investigations would be conducted to incorporate an insulated hot water storage tank to evaluate the system economic viability as a power producer and hot water generator. Temperatures were recorded along the evaporator and condenser sections of the heat pipe, thermoelectric junction temperatures and inlet/outlet water channels. This paper presents the experimental results obtained. Typical daily experimental results showed that electrical output voltage and hot water temperatures peaked around 15.30 before decreasing towards the evening. Total electrical efficiency was very low, about 0.16% at around 15.30 h.